2015
DOI: 10.1007/s10705-015-9674-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimating soil erosion in sub-Saharan Africa based on landscape similarity mapping and using the revised universal soil loss equation (RUSLE)

Abstract: Soil erosion is one of the major forms of land degradation in sub-Saharan Africa (SSA) with serious impact on agricultural productivity. Due to the absence of reliable data at appropriate resolution and differences in the methods used, there are discrepancies in soil erosion estimates at both continental and basin levels. This study attempts to contribute to the existing regional soil erosion estimates based on a two-stage approach. First, we partitioned SSA into environmental units, so-called similar environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 39 publications
5
34
0
1
Order By: Relevance
“…Results of study are also in agreement with Tamene & Le (2015) findings on soil erosion in sub-Saharan Africa, these researchers reported that soil loss ranged from 25-75t/ha/year. However the results are far less than the results obtained by Karamage et al (2016) who observed the average soil loss of 250 t/ha/year in his study on extent of cropland and related soil erosion risk in Rwanda and 490 t/ha/year in his study of usle-based assessment of soil erosion by water in the Nyabarongo River Catchment, Rwanda.…”
Section: Discussionsupporting
confidence: 90%
“…Results of study are also in agreement with Tamene & Le (2015) findings on soil erosion in sub-Saharan Africa, these researchers reported that soil loss ranged from 25-75t/ha/year. However the results are far less than the results obtained by Karamage et al (2016) who observed the average soil loss of 250 t/ha/year in his study on extent of cropland and related soil erosion risk in Rwanda and 490 t/ha/year in his study of usle-based assessment of soil erosion by water in the Nyabarongo River Catchment, Rwanda.…”
Section: Discussionsupporting
confidence: 90%
“…The mean estimates of 39.2 t ha −1 y −1 of soil eroded in 2015 ( Figure 6b) and 41.4 t ha −1 y −1 from Buberuka highlands AEZ (Table A1) are in accordance with the work of Kagabo et al [29], Kabirigi et al [36] and Karamage et al [37], but far less from the results reported by Karamage et al [9,26] ( Table 5). In addition, our findings are relatively comparable with a recent study conducted over the entire East Africa region with a mean soil loss of 34.2 t ha −1 y −1 for Rwanda [83], and in line with mean soil erosion rates ranging between 35 t ha −1 y −1 and 75 t ha −1 y −1 predicted in Sub-Saharan Africa [84]. Comparing the results of Karamage et al [9,26] (Table 4) with the findings of this study and other studies carried out in Rwanda and in the region, suggests that their results may be overestimates, an issue previously highlighted by Kabirigi et al [36].…”
Section: Perspective Of Soil Erosion By Water In Rwandasupporting
confidence: 91%
“…In most of Sub-Saharan Africa, more than 50% of the population heavily relies on local agriculture for food [3], where poor land management usually leads to extreme soil erosion [4]. Today, soil erosion is the major cause of land degradation in Sub-Saharan Africa with serious impacts on agricultural productivity [5]. Numerous studies have highlighted that land conversion to agricultural land use stands as a catalyst for accelerated soil erosion rates [6][7][8][9][10]; and if these agriculture-related erosion rates remain far beyond the rates of soil production, the global society will eventually be compelled to either adopt agricultural methods that sustain the soil or face increasing competition over a shrinking agricultural land base [6].…”
Section: Introductionmentioning
confidence: 99%